Experience, Socialization, Application, and Relevance in Music Education: Supplementary Files - Deal, Madison (My University, 2018)
This lesson plan was based on my music philosophy including the aspects of experience, socialization, application, and relevance. Students used aural skills while sight reading new music and singing dominant to tonic chords during warm up exercises. They created movement emphasizing different musical concepts and analyzed new music. I have grown exponentially as a teacher since I started the Masters’ program at Kansas State University. The two major developments in my teaching have been the paradigm switch from product to process and the cultivation of an environment where students take ownership of learning. My students have become independent musicians due to practicing aural skills, learning music theory, and activating higher-order thinking.
Keywords: Music Education; Philosophy; Experience; Socialization; Application; Relevance